RELATIONSHIP BETWEEN PRINCIPAL LEADERSHIP, WORK ENVIRONMENT, AND WORK DISCIPLINE AND TEACHER WORK ETHICS - RAHMAWATI, Andita (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This research aims to reveal the principal's leadership role, work environment, and work discipline on the work ethic of state high school teachers in Kalideres District. The method used in this study is a quantitative method with data collection using a questionnaire. The question- naire was tested on 30 respondents to test the validity of each statement item. The population in this study were the principals and teachers of public high schools in Kalideres District as many as 112 people. The research sample used simple random sampling. The number of samples taken was calculated using the Slovin formula with a significant level of 5%, namely 87 respondents. In analyzing the research data, normality test analysis, multicollinearity test, multiple lin- ear regression test, correlation test, and f test and t test were used. Based on the results of the study, the following values were obtained: (1) principal leadership (X1) with work ethic (Y) ry1 = 0,9711% ; (2) work environment (X2) with work ethic (Y) ry2 = 0,9774, (3) work discipline (X3) with work ethic (Y) ry3 = 0,9894%; and (4) principal leadership (X1), work environment (X2), and work discipline (X3) with work ethic (Y) ry123 = 0,9920. Based on the calculation results, it is known that together the principal's leadership, work environment, and work discipline have a positive direct relationship with the work ethic of public high school teachers in Kalideres District, West Jakarta.